Análisis multidisciplinario de suelo en calzado como herramienta forense para la reconstrucción de escenarios criminales. - Carrazco Duchitanga, Henry Gabriel (My University, 2025)
This study addresses the potential of shoe soles as reservoirs of microorganisms and their application in forensic investigations for the reconstruction of criminal scenarios. The general objective is to evaluate the applicability of combined analytical techniques (pH, colorimetry, microscopy and NIR spectroscopy) in the characterization of soil samples for their individual identification in forensic chemical expertise, contributing to the resolution of criminal cases. The methodology includes the collection of samples in the Primero de Noviembre sector, Pasaje canton, by means of sterile swabs, detailed microbiological analysis and physicochemical characterization of the adhered soil. The results show the presence of pathogens such as Staphylococcus aureus, Aspergillus spp. and Candida albicans, whose distribution is influenced by factors such as type of footwear, use and environmental conditions. It was established that variables such as soil pH and organic matter accumulation significantly influence microbial proliferation, reinforcing the usefulness of soles as biomarkers of geography and human activity. In conclusion, this work constitutes the first methodological framework in Ecuador to integrate forensic microbiology in criminal investigations, filling a technical gap and laying the groundwork for future developments in scientific justice. As recommendations, it is suggested to continue with similar studies considering different socioeconomic and geographical contexts to expand the forensic microbiological database.
Este estudio aborda el potencial de las suelas de calzado como reservorios de microorganismos y su aplicación en investigaciones forenses para la reconstrucción de escenarios criminales. El objetivo general es evaluar la aplicabilidad de técnicas analíticas combinadas (pH, colorimetría, microscopía y espectroscopía NIR) en la caracterización de muestras de suelo para su identificación individual en peritajes químicos forenses, contribuyendo a la resolución de casos criminales. La metodología incluye la recolección de muestras en el sector Primero de Noviembre, cantón Pasaje, mediante Hisopos estériles, análisis microbiológico detallado y caracterización fisicoquímica del suelo adherido. Los resultados evidencian la presencia de patógenos como Staphylococcus aureus, Aspergillus spp. y Candida albicans, cuya distribución está influenciada por factores como el tipo de calzado, uso y condiciones ambientales. Se estableció que variables como el pH del suelo y la acumulación de materia orgánica influyen significativamente en la proliferación microbiana, reforzando la utilidad de las suelas como biomarcadores geográficos y de actividad humana. En conclusión, este trabajo constituye el primer marco metodológico en Ecuador para integrar la microbiología forense en investigaciones criminales, llenando un vacío técnico y sentando bases en la justicia científica. Como recomendaciones, se sugiere continuar con estudios similares considerando diferentes contextos socioeconómicos y geográficos para ampliar la base de datos microbiológica forense.
Keywords: CALZADO; ESPECTROSCOPIA; MICROBIOLOGIA FORENSE; PH